Remote Sensing and GIS based Morphometric Analysis for Micro-watershed Prioritization in Takarla-Ballowal Watershed - Kushwaha, N. L.; Bhardwaj, Anil (Journal of Agricultural Engineering, 2018)
Micro-watershed prioritization has gained importance in watershed management. Morphometric analysis of the Takarla-Ballowal watershed in Shivalik foot-hills of Punjab was carried out using remote sensing and GIS techniques. ASTER data was used for preparing Digital Elevation Model (DEM). The total area of the watershed (2401.82 ha) was divided into 9 micro-watersheds (MWS-1 to MWS-9) with areas ranging from 88.03 ha to 376.72 ha. Drainage density of the micro-watersheds varied from 11.41 km.km-2 (MWS-1) to 3.97 km.km-2 (MWS-9), elongation ratio from 0.46 (MWS-8) to 0.80 (MWS-1 and MWS-3), circularity ratio from 0.68 (MWS-1) to 0.34 (MWS-7 and MWS-8), and relief ratio (Rh) from 0.013(MWS-9) to 0.070 (MWS-3). The length of overland flow varied from 125.94 m (MWS-9) to 43.82 m (MWS-1). Compound morphometric parameter values of the micro-watersheds were determined based on each morphometric parameter value, and the micro-watersheds ranked. The micro-watershed MWS-6 with compound parameter value of 5.7 had lowest priority, while MWS-1 had highest priority with compound parameter value of 4.3, suggesting that MWS-1 was subjected to maximum soil erosion and susceptible to natural hazards. Hence, the micro-watershed MWS-1 should be given top priority for planning and executing conservation treatments.